Physical, Thermal and Morphology Properties af Polyvinyl Alcohol-Based Composite Enhanced with Collagen and Bromelain for Cartilage Application - Nur Syafiqa Amirah Izam; Hasraf, Nadirul; Hamzah, Syahir (Progress in Engineering Application and Technology, 2023)
This thesis reports the preparation of polyvinyl alcohol (PVA) film modified with collagen and 3% bromelain via solvent casting and surface entrapment method for cartilage application. The concentration of collagen used was varied from 0 to 2% w/v the hydrophilicity properties of the film was observed via swelling test and moisture absorption test. PVA/2%Col with 3% bromelain having good swelling properties in phosphate buffer saline (PBS) solution and have a good results of moisture absorption compared to other films. PVA/2%Col with 3% bromelain concentration was chosen as the optimum PVA/Collagen film and was further tested in order to observe its physical properties. The chemical interaction of the film was analyzed by Fourier Transfrom Infrared Spectroscopy (FTIR). Scanning Electron Microscope (SEM) testing also have been conducted to observe it surface morphology. Differential Scanning Calorimetry (DSC) testing, PVA/2%Col with 3% bromelain film give a better results compared to other films. Futhermore, for In-vitro Biomineralization testing using SEM, PVA/2%Col with 3% bromelain shows good results. These report were clearly suggestive that biopolymers such as PVA can exhibit an increasing of physical properties by treated with collagen and bromelain. This new modified towards the PVA film can enhance its quality and decrease the limitations of application in treating cartilage application.